2011
DOI: 10.1002/met.278
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory diseases in Greater Buenos Aires and meteorological variables

Abstract: This paper provides a preliminary assessment of the relationship between atmospheric conditions and respiratory diseases based on the analysis of disease occurrence in patients during the period August 2004 to September 2007. To this effect, medical records from a medical services firm were examined, as well as temperature data (daily, maximum, minimum, dew point), pressure and relative humidity, measured at the meteorological station of Ezeiza (34.49°S, 58.32°W). The analysis revealed a strong seasonal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Estudos nacionais tem verificado associações positivas entre as condições climáticas e doenças respiratórias (MOURA et al, 2008;CASTRO et al,2009;SOUSA et al,2012). No âmbito internacional também encontramos alguns esforços (ALESSANDRO, 2012;ZHU et al, 2012;SALVI, 2007).…”
Section: Mudanças Climáticas E Doenças Associadasunclassified
See 1 more Smart Citation
“…Estudos nacionais tem verificado associações positivas entre as condições climáticas e doenças respiratórias (MOURA et al, 2008;CASTRO et al,2009;SOUSA et al,2012). No âmbito internacional também encontramos alguns esforços (ALESSANDRO, 2012;ZHU et al, 2012;SALVI, 2007).…”
Section: Mudanças Climáticas E Doenças Associadasunclassified
“…Concluíram que o modelo desenvolvido é potencialmente útil para projetar as consequências de cenários de mudança climática e oferecendo insights sobre a susceptibilidade aos efeitos adversos do clima. Alessandro (2012) que avaliou a relação entre as condições atmosféricas e doenças respiratórias na cidade de Buenos Aires com base na análise de ocorrência da doença em pacientes durante o período de agosto de 2004 a setembro de 2007. Os resultados revelam uma forte relação sazonal, com valores máximos nos meses mais frios do ano e os valores mínimos no verão.…”
Section: De Acordo Comunclassified
“…McMichael and Lindgren 14 used the 95th percentile above the air temperature distribution as the threshold value for the heat effect and the fifth percentile below the air temperature distribution as the threshold value for the cold effect, whereas Azongo et al 15 used the 75th percentile and the 25th percentile as the threshold values for the heat effect and cold effect, respectively. Alessandro 16 found that there is a strong seasonal correlation between air temperature and the incidence of respiratory diseases. The number of patients peaked when the temperature was low in the winter, and there were fewer patients when the temperature was high in the summer.…”
mentioning
confidence: 99%